Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

rcb95

  • 3 years ago

If f(x) = x² + 1 and g(x) = 3x + 1, find f(-1) + 5g(-3).

  • This Question is Closed
  1. eroshea
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    1.substitute x=-1 in f(x)=x^2+1 ----> f(-1)=(-1)^2+1 2. substitute x= -3 in g(x)=3x+1 ----> g(-3)=3(-3)+1 3. in finding f(-1) + 5g(-3) just substitute what u had solved in 1 and 2

  2. ali_hassan
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    f(-1)=(-1)^2+1=2 g(-3)=3(-3)+1=-9+1=-8 5g(-3)=5(-8)=-40 f(-1)+5g(-3)=2-40=-38

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy